The complete project manager : integrating people, organizational, and technical skills - Englund, Randall L. (Management Concepts Press, 2012)
Get proven procedures to overcome project challenges The Complete Project Manager: Integrating People, Organizational, and Technical Skills is the practical guide that addresses the "soft" project management skills that are so essential to successful project, program, and portfolio management. Through a storytelling approach, the authors explain the necessary skills-and how to use them-to create an environment that supports project success. They demonstrate both the "why" and the "how" of creatively applying soft project management skills in the areas of leadership, conflict resolution, negoti
Keywords: Project management.; elektronické knihy; electronic books